Global Surgeon Opinion on the Impact of Surgical Access When Using Endocutters Across Specialties - Marina Gutierrez; Nadine Jamous; William Petraiuolo; Sanjoy Roy (Journal of Health Economics and Outcomes Research, 2023)
**Background:** Despite design enhancements in endocutters, key challenges related to limited surgical access and space can impact stapling and, potentially, surgical outcomes. **Objectives:** This study aimed to develop consensus statements outlining the clinical value of precise articulation and greater anatomical access in minimally invasive surgery performed by bariatric, colorectal, and thoracic surgeons. **Methods:** Colorectal, bariatric, and thoracic surgeons from Japan, the United States, United Kingdom, and France participated in a 2-round modified Delphi panel. Round 1 included binary, Likert scale–type, multiple-response, and open-ended questions. These were converted to affirmative statements for round 2 if sufficient agreement was reached. Consensus was set at a predefined threshold of at least 90% of panelists across all surgical specialties and regions selecting the same option ("agree" or "disagree") for the affirmative statements. **Results:** Of the 49 statements in the round 2 questionnaire, panelists (n=135) reached consensus that (1) tissue slippage outside stapler jaws can occur due to limited access and space; (2) greater jaw aperture could help to manipulate thick or fragile tissue more easily; (3) articulation of an endocutter is clinically important in laparoscopic surgeries; (4) improved access to hard-to-reach targets and in limited space would improve safety; and (5) an endocutter with improved access through greater articulation would become common use. **Discussion:** By understanding user-specific challenges and needs from both specialty- and region-wide perspectives, endoscopic stapling devices can continue to be refined. In this study, improved articulation and greater jaw aperture were the key design features examined. Improved articulation and greater jaw aperture were key stapler design features identified in this study that may mitigate the risk of instrument clashes and intraoperative complications such as anastomotic leaks. **Conclusions:** This study gained insights into surgeons' perspective across a variety of specialties and from 3 distinct geographies. Participating surgeons reached consensus that an endocutter with greater jaw aperture and articulation may improve surgical access and has potential to improve surgical outcomes.